Morality and the emotions - Bagnoli, Carla, 1966- (New York ; Oxford : Oxford University Press, 2011)
Emotions shape our mental and social lives, but their relation to morality is problematic: are they sources of moral knowledge or obstacles to morality? Fourteen original articles by leading scholars in moral psychology and philosophy of mind explore the relation between emotions and practical rationality, value autonomy, and moral identity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Emotions -- Moral and ethical aspects; Emotions -- Philosophy; Ethics